2017
DOI: 10.14527/pegegog.2017.004
|View full text |Cite
|
Sign up to set email alerts
|

Examining secondary school students' safe computer and internet usage awareness: An example from Bartın province

Abstract: Information and Communication Technologies (ICT) have been rapidly prevailed among the children and youths. Personal technologies facilitating the students to gain some learning experiences both in and out of the schools also include many threats. It is important for students to have high awareness of safe internet and computer use to overcome with these threats. In this research, it was aimed to reveal internet security and computer usage awareness profiles of students studying in the secondary school.  The d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
13
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 22 publications
(64 reference statements)
0
13
0
4
Order By: Relevance
“…The researchers state that children in Turkey are confident about their use of Internet, but their Internet skills are neither sufficient nor efficient to overcome the risks they have encountered on the Internet. In similar researches conducted on different age groups nationwide in Turkey, similar results have been collected and it is stated that students have a low awareness of safe Internet use and they are confronted with various risks on the Internet (Google, MEB, & IGK, 2015;Gökçearslan & Seferoğlu, 2015;Yılmaz, Karaoğlan-Yılmaz, Öztürk, & Karademir, 2017). In a study in another field, which was undertaken to determine the extent to which institutions and organizations have given their periods to the privacy of individuals, Karlıdağ (2014) has examined the web pages of 16 Metropolitan Municipalities and their affiliated municipalities.…”
Section: Introductionmentioning
confidence: 72%
See 1 more Smart Citation
“…The researchers state that children in Turkey are confident about their use of Internet, but their Internet skills are neither sufficient nor efficient to overcome the risks they have encountered on the Internet. In similar researches conducted on different age groups nationwide in Turkey, similar results have been collected and it is stated that students have a low awareness of safe Internet use and they are confronted with various risks on the Internet (Google, MEB, & IGK, 2015;Gökçearslan & Seferoğlu, 2015;Yılmaz, Karaoğlan-Yılmaz, Öztürk, & Karademir, 2017). In a study in another field, which was undertaken to determine the extent to which institutions and organizations have given their periods to the privacy of individuals, Karlıdağ (2014) has examined the web pages of 16 Metropolitan Municipalities and their affiliated municipalities.…”
Section: Introductionmentioning
confidence: 72%
“…Araştırmacılar Türkiye'de çocukların internet kullanımı konusunda kendilerine güvendiklerini ancak internet becerileri konusunda yeterli olmadıklarını ve karşılaştıkları risklerin üstesinden gelmekte yetersiz kalabileceklerini ifade etmektedirler. Türkiye'de ulusal olarak farklı yaş grupları üzerinde yapılan araştırmalarda da benzer bulgular elde edilerek öğrencilerin güvenli internet kullanma farkındalıklarının düşük seyrettiği ve internet ortamında çeşitli risklerle karşı karşıya oldukları belirtilmektedir (Google, MEB, & IGK, 2015;Gökçearslan & Seferoğlu, 2015;Yılmaz, Karaoğlan-Yılmaz, Öztürk, & Karademir, 2017). Bir başka alanda, kurum ve kuruluşların bireylerin gizliliklerine ne derece dönem verdiklerini belirlemek için yapılan çalışmada ise Karlıdağ (2014), 16 Büyükşehir Belediyesi ile onlara bağlı belediyelerin web sayfalarını incelemiştir.…”
unclassified
“…In this respect, the results regarding men's protection of their privacy in literature could be said to support the related results obtained in the present study. In one study carried out on the secure use of information and communication technologies, it is reported that students tend to avoid taking privacy and security measures because of their lack of awareness of secure Internet use (Yılmaz, Karaoğlan Yılmaz, Öztürk & Karademir, 2017). Considering the fact that social network environments are used by the new-generation learners intensively both for educational purposes and for communication and entertainment purposes, the importance of the dimensions of social identity becomes more prominent.…”
Section: Discussionmentioning
confidence: 99%
“…Bu doğrultuda erkeklerin gizliliğin korunmasına yönelik sonuçlarının, bu çalışmadaki bulgularla benzerlik gösterdiği söylenebilir. Bilgi ve iletişim teknolojilerinin güvenli kullanımına ilişkin yapılan bir çalışmada öğrencilerin gizlilik ve güvenlik önlemleri almamalarının sebebinin güvenli internet kullanımına yönelik farkındalıklarının yeterli olmamasından kaynaklandığı ifade edilmektedir (Yılmaz, Karaoğlan Yılmaz, Öztürk & Karademir, 2017). Sosyal ağ ortamlarının yeni nesil öğrenenler tarafından hem öğrenme hem de iletişim ve eğlence amaçlı yoğun olarak kullanıldığı düşünüldüğünde; sanal kimliğin boyutlarının önemi daha net ortaya çıkmaktadır.…”
Section: Discussionunclassified
“…A primary example of these is cyber bullying (Durak & Seferoğlu, 2016). Children can create threats to their own security and others' personal information by using technology unconsciously (Karaoğlan Yılmaz, Çavuş Ezin, 2017;Karaoğlan-Yılmaz, Yılmaz, & Sezer, 2014;Yılmaz, Karaoğlan-Yılmaz, Öztürk, & Karademir, 2017). At this point, it is important that children use technology ethically and consciously (Forgays, Hyman, & Schreiber, 2014).…”
Section: Introductionmentioning
confidence: 99%